Assessing operating theatre efficiency: a prospective cohort study to identify intervention targets to improve efficiency. Issue 11 (1st June 2021) - Wallace, Lauren; Muir, Mathew; Romano, Linda; Wyllie, Tracey; Gyomber, Dennis; Hodgson, Russell
Abstract: Background: Operating theatre efficiency is critical to providing optimum healthcare and maintaining the financial success of a hospital. This study aims to assess theatre efficiency, with a focus on staff activities, theatre utilisation and case changeover. Methods: Theatre efficiency data were collected prospectively at a single centre in metropolitan Melbourne, Australia, over two 5‐week periods. Characteristics of each case and various time points were collected, corresponding to either in‐theatre staff activities or patient events. Results: Two hundred and ninety‐nine cases were prospectively audited over a range of surgical specialties. Setting up represented 42.4% (37.28 min), operating time 40.1% (35.28 min) and finishing up time 17.5% (15.43 min). Theatres were empty (turnover time) for 17.42 min, which was 39.4% of the non‐operative time between operations (44.25 min, turnaround time). Plastic surgery operations required the shortest set‐up and finishing times on most of the measured metrics, with general surgery and obstetrics/gynaecology having longer times. List order made a significant difference, with efficiency improving over the list and over the day for separate am and pm lists. When a patient was not on time to theatre, efficiency in both set up and finishing up metrics was significantly worse. Conclusions: A large proportion of theatre time was being spent on non‐operative tasks, making staff activities potential targets for operating theatre improvement interventions. Motivation and team familiarity were identified as the major factors behind efficiently run operating theatres, supporting the use of regular operating teams and maintenance of a highly motivated workforce. Abstract : Running operating theatres efficiently is complex as shown by this prospective observational study. While a large proportion of theatre time is spent on non‐operative activities suggesting staff activities could be improved, this study found that staff motivation and team familiarity were more important to efficiently run operating theatres.